Clinical and microbiological characteristics of Aeromonas bacteremia in Turkey - Kaya, Abdurrahman; Yıldız Kaya, Sibel; Zerdali, Esra; Koç, Alper; Çağlar, Bilge; Ertürk, Ümran Şümeyse; Yılmaz, Mesut; Aygün, Gökhan; Balkan, İlker İnanç; Mete, Bilgül; Saltoğlu, Neşe; Mert, Ali; et al. (Akademiai Kiado Zrt, 2021)
We investigated the cases with Aeromonas bacteremia in terms of clinical and microbiological characteristics, underlying disease and mortality rates. Patients with positive blood cultures were included in this research. Aeromonas bacteremia was diagnosed as at least one positive blood culture for Aeromonas species. The bacteremia was defined as community origin if the onset was in the community or within 72 hours of hospital admission. The others were considered as nosocomial. All bacteria were defined as Aeromonas with conventional method. Species identification was verified by VITEK system. Antibiotic susceptibility tests were analyzed with the disc diffusion, E-test method or VITEK system. Thirty-three patients were diagnosed with bacteremia due to Aeromonas spp. Hematologic and solid tumors were the leading underlying conditions, followed by cirrhosis. Two patients (6%) had community-acquired infections. Aeromonas hydrophila was the most common isolated bacterium. The crude mortality rate was 36%. 12 patients died and 6 deaths and 4 deaths were detected in patients with bacteremia caused by A. hydrophila and Aeromonas sobria respectively. All strains were resistant to ampicillin and more than 90% of the strains were susceptible to trimethoprim-sulfamethoxazole, fluoroquinolone, third generation cephalosporins, and carbapenems. Aeromonas sp. is not a frequent cause of bacteremia however, it may lead to high mortality rates, especially in the immunocompromised hosts and patients with liver cirrhosis. Nosocomial Aeromonas bacteremia is not uncommon in these populations. Broad-spectrum cephalosporins, piperacillin-tazobactam, fluoroquinolones, and carbapenems remain as effective antimicrobial agents for therapy of Aeromonas bacteremia.
Keywords: Aeromonas Spp; Bacteremia; Antibiotic; Infection; Nosocomial